2021
DOI: 10.1016/j.brachy.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Salvage low-dose-rate brachytherapy for local recurrences after prostatectomy and adjuvant or salvage external beam irradiation: Feasibility study on five patients and literature review

Abstract: PURPOSE: To assess the feasibility and tumor outcome of re-irradiation with low-dose-rate brachytherapy for macroscopic local recurrences after radical prostatectomy (RP) followed by adjuvant or salvage external beam radiation therapy (EBRT). METHODS AND MATERIALS: Between 2011 and 2018, five men with histologically proven local failure within the prostate (4) or seminal vesicle bed (1) after RP and adjuvant or salvage EBRT (median dose: 67.5 Gy) underwent a salvage brachytherapy (S-BT). The median delay after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…For instance, one study assessed the feasibility of salvage surgery, with a comparable median of biochemical recurrence-free survival of 23.7 months [29]. Another study reported the feasibility of brachytherapy with five patients, which is not enough to make conclusions on efficacy and safety [30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study assessed the feasibility of salvage surgery, with a comparable median of biochemical recurrence-free survival of 23.7 months [29]. Another study reported the feasibility of brachytherapy with five patients, which is not enough to make conclusions on efficacy and safety [30].…”
Section: Discussionmentioning
confidence: 99%
“…With a median follow-up of 21 months, local control was achieved in 3/4 of evaluable patients. No grade 3 acute toxicity and Grade 2 or more late toxicities were observed (12).…”
Section: Discussionmentioning
confidence: 90%
“…Palliative androgen deprivation therapy (ADT) (continuous or intermittent) is the salvage treatment proposed in most cases (9,10). Curative strategies including surgery, brachytherapy, HIFU or cryotherapy are feasible, but lack a good level of evidence (11)(12)(13). More recently, salvage stereotactic prostate bed radiotherapy was shown to be feasible with acceptable toxicity and encouraging e cacy results in retrospective studies (5,14).…”
Section: Introductionmentioning
confidence: 99%
“…In majority of patients, this method was used as a boost combined with EBRT, except for one recent study [9][10][11][12]. On the contrary, salvage low-dose-rate (LDR) seeds were mostly used without EBRT [13][14][15][16][17][18]. Following RP and EBRT as adjuvant or salvage treatment, it is challenging to choose a further local treatment.…”
Section: Purposementioning
confidence: 99%